Acoustic Dispensing Preserves the Potency of Therapeutic Peptides throughout the Entire Drug Discovery Workflow. (February 2016) - Naylor, Jacqueline; Rossi, Alessandra; Hornigold, David C.
Routine peptide structure-activity relationship screening requires the serial dilution of peptides to produce full concentration-response curves. Established tip-based protocols involve multiple tip changes and high exposure to plasticware. In the case of peptides, this becomes a challenge, since peptides can adsorb to plastic, resulting in an observed loss of potency. Various methods can be employed to prevent peptide loss during compound handling, such as the inclusion of bovine serum albumin or solvents in assay buffer and the siliconization of plasticware, yet protein binding remains unpredictable. The degree of variation by which peptides will adhere to plasticware can confuse results and cause inaccuracies in potency predictions. We evaluated acoustic noncontact methods for peptide serial dilution and compared it with traditional tip-based methods, on the effect on potency curves for glucagon-like peptide-1 and glucagon peptide analogues. The current study demonstrates the benefits of noncontact dispensing for high-density microplate assay preparation of peptides using nanoliter droplets across our entire drug discovery workflow, from in vitro high-throughput screening to drug exposure determinations from in vivo samples.